Investigation of CRISPR-Cas adaptation mechanism through exploration of Cas4-1 fusions - Walker, Emily (2019)
CRISPR-Cas is an adaptive immune system present in bacteria and archaea. It involves two linked stages: adaptation and interference. Adaptation generates a database of mobile genetic element sequences within a CRISPR locus through ‘capture’ of DNA fragments by Cas1-Cas2 and integration into the CRISPR locus. The CRISPR locus is transcribed and separated into individual units, called crRNA. During interference crRNA bound within ‘interference’ ribonuceloprotein complexes targets DNA from Mobile genetic elements (MGE) through complementary base pairing between crRNA and the MGE before degradation of the target.